‘New Normal’ in a Hospitality with Family Management in Graha Dewata Juwana Hotel - I Gusti Ketut Indra Pranata Darma (Masyarakat Pariwisata : Journal of Community Services in Tourism, 2021)
The hospitality industry is one part of the world of tourism which plays an important role wherever located. The role of the hospitality industry is not only as a place to stop and rest, but it is a beginning of the economic activities of other industries. The arrival of covid-19 virus in early 2020, no doubt hit all the industrial sectors in the world including the hospitality industry. For almost 3 months, people in the world are forced to live in fear of the covid-9 virus. The World Health Organization (WHO) also called for "New Normal" as a new form of adaptation for all people in the world to this virus until a cure is found. Based on the presence of the virus, the hotel industry has welcomed "New Normal" by following strict rules in force following local government recommendations. This research will try to find out the form of the "New Normal" protocol in the hotel industry, especially in the management of family hotels in Juwana, which is one of the areas defined in the red zone. So we get the right steps to be applied to other regions by following the prevailing customs in the area.